Moderating of Inflation Policy and Its Relation to the Effect of Interest Rate and Exchange Rate on Decreasing IHSG - Subhan, Nuruddin (Universitas Mercu Buana, 2024)
Objectives: The objectives of this research are: 1) to determine the effect of interest rates on the IHSG; 2) to determine the effect of the exchange rate on the IHSG; 3) to know the effect of the interest rate on the IHSG with inflation as moderation; and 4) knowing the effect of the exchange rate on the IHSG with inflation as moderation. Methodology: This research methodology was carried out using a quantitative model with a moderating effect analysis method which was processed using SmartPLS 3.0. The research findings and conclusions show that the significance value of interest rates is 0.747>0.05, which means that interest rates do not influence the IHSG. This means that interest rate movements during 2017-2022 are stable so that it does not cause investors to withdraw shares which has an impact on weakening the IHSG. Furthermore, the significance value of the exchange rate is 0.010<0.05, which means that there is an influence of the exchange rate on the IHSG. This is caused by the instability of the exchange rate in Indonesia during 2017-2022, because an increase in the exchange rate means that dividends distributed will decrease and investors will withdraw their shares, resulting in a weakening of the IHSG. Finding: The moderation of inflation on the effect of interest rates on the IHSG obtained a significance value of 0.000<0.05. Likewise, the moderation of inflation on the impact of the exchange rate on the IHSG obtained a significance value of 0.000<0.05. Conclusion: Inflation significantly moderates the influence of the interest rate and the exchange rate on the IHSG